Molecular dynamics simulations shed light into the donor substrate specificity of vertebrate poly-alpha-2,8-sialyltransferases ST8Sia IV - Teppa, Roxana Elin; Galuska, Sebastian Peter; Harduin-Lepers, Anne (Biochimica et biophysica acta. General subjects, 2024)
Sialic acids are essential monosaccharides influencing several biological processes and disease states. The sialyltransferases catalyze the transfer of Sia residues to glycoconjugates playing critical roles in cellular recognition and signaling. Despite their importance, the molecular mechanisms underlying their substrate specificity, especially between different organisms, remain poorly understood. Recently, the human ST8Sia IV, a key enzyme in the synthesis of polysialic acids, was found to accept only CMP-Neu5Ac as a sugar-donor, whereas the whitefish Coregonus maraena enzyme showed a wider donor substrate specificity, accepting CMP-Neu5Ac, CMP-Neu5Gc, and CMP-Kdn. However, what causes these differences in donor substrate specificity is unknown. Computational approaches were used to investigate the structural and biochemical determinants of the donor substrate specificity in ST8Sia IV. Accurate structural models of the human and fish ST8Sia IV catalytic domains and their complexes with three sialic acid donors (CMP-Neu5Ac, CMP-Neu5Gc, and CMP-Kdn) were generated. Subsequently, molecular dynamics simulations were conducted to analyze the stability and interactions within these complexes and identify differences in complex stability and substrate binding sites between the two ST8Sia IV. Our MD simulations revealed that the human enzyme effectively stabilizes CMP-Neu5Ac, whereas CMP-Neu5Gc and CMP-Kdn are unstable and explore different conformations. In contrast, the fish ST8Sia IV stabilizes all three donor substrates. Based on these data, we identified the key interacting residues for the different Sias parts of the substrate donors. This work advances our knowledge of the enzymatic mechanisms governing sialic acid transfer, shedding light on the evolutionary adaptations of sialyltransferases. •Human and salmonid ST8Sia IV have different sugar-nucleotide donor specificity.•MD simulations highlight significant differences between highly mobile regions of human and fish ST8Sia IV.•Human ST8Sia IV shows a narrow specificity towards CMP-Neu5Ac donor substrate.•Fish ST8Sia IV forms stable complexes with CMP-Neu5Ac, CMP-Neu5Gc, and CMP-Kdn.•Family motif “a” contains key residues to stabilize different Sia parts of the donor.